Development of Poly(aniline-co-o-toluidine)/TiO2 nanocomposite coatings for low carbon steel corrosion in 3.5% NaCl solution. Issue 23 (2nd December 2018) - Aslam, Jeenat; Lone, Irfan Hussain; Radwan, Nagi; Mobin, Mohammad; Zehra, Saman; Aslam, Ruby
Abstract: Chemical oxidative polymerization of aniline (AN) and o-toluidine (OT) for the synthesis of copolymer, Poly(AN-co-OT) and its composite with TiO2 nanoparticles, Poly(AN-co-OT)/TiO2 employing ammonium persulfate as an oxidant and HCl as an external dopant were carried out. The homopolymers, Polyaniline and Poly(o-toluidine) were also prepared by following similar method. The synthesized polymers were characterized with FTIR spectroscopy, XRD/SEM/TEM analysis. The anticorrosive coatings were synthesized in dimethyl sulfoxide solution by dissolving synthesized polymers, and then were applied on low-carbon steel (LCS) samples using epoxy binder. The anticorrosive potential of the polymer coatings containing copolymer, copolymer-nanocomposite and homopolymers on LCS was evaluated in 3.5% NaCl at a temperature of 30 °C by open circuit potential, electrochemical impedance spectroscopy and potentiodynamic polarization measurements. It was observed that the nanocomposite coating increases the protection efficacy by providing better barrier properties against corrosion as compared with neat copolymer and homopolymers coatings. The morphology of the coatings before and after 60 days LCS immersion in 3.5% NaCl solution was determined using SEM.